GROWTH OF A POPULATION OF Cabralea canjerana IN A NATURAL REGENERATION STAGE IN THE SECONDARY FOREST WITH USE OF THE LIBERATION - Zimmermann, Anna Paula Lora; Fleig, Frederico Dimas (Floresta, 2019)
This work aimed to verify the influence of the liberation technique on the growth of a young population of Cabralea canjerana, based on this to determine the best size for the plants to be liberated and to verify the differences in growth between emergent and dominate plants. The liberation consisted of the clear cutting of all species different from the species of interest, with 90 trees from the species being liberated and 73 being kept in competition (control). The variables total height and diameter at 10 cm from the soil were previously and annually, for four years after the liberation, measured. At the end of the experiment the crown diameter, crown length and branch insertion height were measured and the trees were classified according the treatment and sociological position (emergent or dominated). The data were submitted to means tests in the statistical package SISVAR. Liberated plants showed a higher increase in diameter or height than not liberated trees. However, the increase gain in diameter and height is higher when realized in plants up to 100 cm high, especially if the plants are able to become emergent. Not liberated emergent trees showed higher branch insertion height in the stem, which in practice shows a higher proportion of stem free from nodes. Thus, it is concluded that the liberation stimulates the growth of young trees of C. canjerana.